An analysis of factors affecting the investment growth of Indonesian Islamic insurance - Abdullah, Zaki (Journal of Islamic Economics Lariba, 2018)
The development of Islamic insurance undergoes a noticeable growth of investment. As Islamic insurance companies have a better ability to manage investments, it is predictable that the companies will be able to better grow assets. The objective of this study is to analyze the factors that influence the growth of Islamic insurance investment in Indonesia. This study used an Ordinary Least Square (OLS) method along with the monthly timeline data from January 2014 until October 2016. The results of this study show that a variable yield of mudharabah and an industrial production index enhance a positive impact on the Islamic insurance investment growth. While the inflation, BI rate, and oil price variables negatively affect the growth of Islamic insurance investment.